Health in the province of Tungurahua and its importance in local economic development - Coello Gómez, Gladys (2017)
Health is not only about the absence of disease, but is a component of human capital, which is determined by the circumstances or the environment in which people are born, grow, live, work and age, including the health system, whose characteristics are the result of the distribution of wealth, power and resources. This investigation shows an observation of health situation in Tungurahua´s population, a key factor of local economic development. DOI: https://doi.org/10.31164/bcoyu.13.2017.631 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/631